Perceived roles and professional identity of psychiatric mental health nurses in selected hospital-based psychiatric settings in Metro Manila - Mabale, Maria Angela A.
The increasing demand for mental health services worldwide and the continuing development of government policies for mental health require a huge contribution from psychiatric mental health nurses. However, previous studies reveal that the roles of psychiatric mental health nurses lack distinctiveness compared with other members of the health care team thus the need for clearer identification of their role and professional identify. This study intended to describe the perceived roles of psychiatric mental health nurses in selected hospital-based psychiatric settings, describe their professional identity in comparison with other mental health professionals and explore opportunities and future directions for advanced practice psychiatric nursing in the Philippines. -- Qualitative descriptive study design was used. A purposive sample of eleven (11)psychiatric mental health nurses and twelve (12) non-nurse (i.e. psychiatrists, clinical psychologists, social worker, and occupational therapists) participated in semi-structured interviews about their perceived roles and professional identity of psychiatric mental health nurses and the future directions and opportunities for advanced practice psychiatric nursing in the Philippines. Content analysis was used to analyze the data. -- It was found out that the perceived roles of psychiatric mental health nurses are direct care provider, facilitator of family and therapeutic group activities, manager of therapeutic environment, educator, collaborator, patient advocate and researcher. It also showed that the professional identity of the psychiatric mental health nurses is clearly established in hospital-based psychiatric settings and there is a strong collaboration within the team members based on the participants’ experiences. Lastly, it was emphasized that the provision of mental health services in the community is an opportunity for advanced practice psychiatric nursing though follow-up care, mobilization of community resources and promotion of mental health.